Digital Marketing Dan Digital Finance Apakah Menjadi Faktor Berkembangnya UMKM Di Surabaya? - Kautsar, Achmad (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2022)
The growth of MSMEs going digital after the Covid 19 pandemic is interesting to study. The importance of digital marketing and digital finance factors provides distinct advantages for MSMEs to explore the digital space through digital marketing practices and neater financial records, resulting in increased MSME performance. The research method is explanatory research with the population of this study being Medium, Small and Micro Enterprises in Surabaya. The sampling technique was carried out by means of random sampling. The sample size in this study was 100 samples which were analyzed using multiple regression. The findings of this study show that digital marketing and digital finance both have a significant positive influence.